Relire pour nous relier - Cassandre Martigny (Glad!)
Through a comparative study of three rewritings of Sophocles’ Oedipus Rex – The Name of Oedipus (1978) by Hélène Cixous, Jocaste (1981) by Michèle Fabien and Jocaste Reine (2009) by Nancy Huston – this article shows how the myth of Jocasta has been enhanced by new interpretations arising from dialogues between these works and with those of their predecessors. The three rewritings denounce patriarchal readings of the myth of Jocasta and create other networks of meanings derived from or set against them. This article will analyse how these authors unravel the source texts to weave a new text that gives voice to the character itself and restores the place of love and couple relationships through a liberating language. The « constellation », understood as a critical paradigm, emphasizes this dialogue between past and present, between the text and its readings and interpretations. It shows the bonds that are created and the impossibility of fixating a myth that is perpetually reshaping itself.